2006
DOI: 10.1016/j.aquaculture.2006.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Pigmenting efficacy of astaxanthin fed to rainbow trout Oncorhynchus mykiss: Effect of dietary astaxanthin and lipid sources

Abstract: The aim of the present experiment was to investigate the effect of two different dietary types of oil (fish oil (FI) and olive oil (OL)) on the pigmenting efficacy of astaxanthin from the green micro-algae Haematococcus pluvialis (ALG) (total amount of carotenoid pigments 32 mg kg − 1 on a dry weight basis of which astaxanthin accounted for 98.6%) and from the synthetic astaxanthin (AST) in terms of astaxanthin serum concentration, induced muscle colour, and astaxanthin muscle retention in rainbow trout for 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 29 publications
6
52
3
2
Order By: Relevance
“…The color values are well within the range reported for rainbow trout in other studies involving astaxanthin [6,11,12,16,17]. Although the results from this study are likely applicable to other strains of rainbow trout, the influence of other dietary factors on astaxanthin absorption and ultimately fillet coloration could potentially influence the results if different diets are used [18].…”
Section: Discussionsupporting
confidence: 79%
“…The color values are well within the range reported for rainbow trout in other studies involving astaxanthin [6,11,12,16,17]. Although the results from this study are likely applicable to other strains of rainbow trout, the influence of other dietary factors on astaxanthin absorption and ultimately fillet coloration could potentially influence the results if different diets are used [18].…”
Section: Discussionsupporting
confidence: 79%
“…In our experiment, we did not find any correlation between colour measurements and fat content of the flesh. Other papers reported that muscle colour attributes were more affected by the astaxanthin source than by the oil source; this was reported by Choubert et al (2006) who ascertained that trout fed on synthetic astaxanthine showed higher chroma (C*), redness and yellowness than fish fed on feed supplemented with astaxanthin from the green micro-algae Haematococcus pluvialis. Using other natural pigmenting compounds, such as red pepper, in comparison with commercial astaxanthin, Yanar et al (2007) observed that the fillet colour was lighter.…”
Section: Discussionmentioning
confidence: 91%
“…Animals cannot synthesize carotenoids, and these pigments must therefore be added to the feeds of farmed species, including aquacultured salmon [45][46][47][48][49][50]. The color of the meat of salmon and trout is an essential demand for customers [39], and for this reason the aquaculture industry requires substantial amounts of carotenoids as animal feed additives per year.…”
Section: Introductionmentioning
confidence: 99%